PENGARUH OPERATING CAPACITY, SALES GROWTH DAN FIRM SIZE TERHADAP FINANSIAL DISTRES (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI 2020-2023) - Hasibuan, Mutiara Hikmah; Ritonga, Mulkan; Mulya Rafika (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the influence of operating capacity, sales growth, and firm size on financial distress in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The analysis method used is multiple linear regression with a quantitative approach. The results of the study show that operating capacity has a negative and significant effect on financial distress, which indicates that operational efficiency contributes to reducing the level of financial pressure of the company. Meanwhile, sales growth has a positive but insignificant influence, showing that sales growth does not necessarily play a direct role in reducing the risk of financial distress. On the other hand, firm size has a positive and significant effect on financial distress, suggesting that large-scale companies are more susceptible to financial pressure, likely due to operational complexity and higher financial burdens. These findings provide important implications for company management in formulating efficiency strategies and more adaptive organizational structures to reduce potential financial distress risks in the mining sector